2019
DOI: 10.13080/z-a.2019.106.022
|View full text |Cite
|
Sign up to set email alerts
|

Role of phytohormones in the formation of dwarf and tall Siberian crabapple (Malus bаccata L. Borkh.)

Abstract: Peculiarities of hormonal status of dwarf and winter hardy trees of Siberian crabapple (Malus baccata L. Borkh.) were studied. The research was carried out on plants growing in the natural habitat (western Transbaikalia, 2009(western Transbaikalia, -2010 and in a cultivated orchard (Irkutsk city, 2012(Irkutsk city, -2013. The study showed that dwarfism is caused by a decline in indole-acetic acid (IAA) content and by the associated changes in the IAA:ABA (abscisic acid) content ratio in the crabapple plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The interactions between and cross-effects of plant hormones can significantly affect plant growth processes (Zhang et al, 2015), and it has been suggested that the ratio of the endogenous content of IAA to ABA in plants is closely related to plant dwarfing (Tworkoski and Fazio, 2016). Previous investigators found that crabapple dwarfing was due to a decrease in the endogenous IAA content and changes in the IAA:ABA ratio under both growth conditions (Rudikovskii et al, 2019). Our experimental results showed that after external application of IAA, GA3 and BR, at 20 d, the IAA:ABA ratio in the treated plants were significantly higher than those in D-CK plants, and the IAA:ABA ratio was significantly and positively correlated with mutant plant height, which further confirmed that exogenous hormones affected endogenous hormones in dwarfing mutants and regulated plant height.…”
Section: Relationship Between Relative Content Of Endogenous Hormones...mentioning
confidence: 99%
“…The interactions between and cross-effects of plant hormones can significantly affect plant growth processes (Zhang et al, 2015), and it has been suggested that the ratio of the endogenous content of IAA to ABA in plants is closely related to plant dwarfing (Tworkoski and Fazio, 2016). Previous investigators found that crabapple dwarfing was due to a decrease in the endogenous IAA content and changes in the IAA:ABA ratio under both growth conditions (Rudikovskii et al, 2019). Our experimental results showed that after external application of IAA, GA3 and BR, at 20 d, the IAA:ABA ratio in the treated plants were significantly higher than those in D-CK plants, and the IAA:ABA ratio was significantly and positively correlated with mutant plant height, which further confirmed that exogenous hormones affected endogenous hormones in dwarfing mutants and regulated plant height.…”
Section: Relationship Between Relative Content Of Endogenous Hormones...mentioning
confidence: 99%
“…Phytohormones play pivotal roles in plant growth and architecture [133]. Among these, gibberellins (GAs) are recognized for their ability to stimulate plant elongation [2].…”
Section: Tree Growth and Developmentmentioning
confidence: 99%
“…W hen compared to MM 106 trees, root-and shootspecific abscisic acid (ABA) deliveries in M 9 composite trees were considerably greater and the increased ABA import corresponded briefly with earlier shoot growth cessation in M 9 composite trees (Else et al, 2018). Dwarfism in crabapple plants is induced by a decrease in indole-acetic acid (IAA) concentration and variations in the IAA:ABA (abscisic acid) content ratio (Rudikovskii et al, 2019). The 'Nantong-xiaofangshi' interstock influences water conductance and gene expression in the grafted scion associated to IAA and Gibberellic acid (GA) metabolism and transduction, hence regulating phytohormone levels and causing dwarfing (Shen et al, 2019).…”
Section: Phytohormonesmentioning
confidence: 99%